Occupational Exposure to Arsenic in Moi University and University of Eldoret Instructional Laboratories and Potential Carcinogenic Risks - Nthenya, S.; Simiyu, G. M.; Otieno , C. A. (African Journal of Education,Science and Technology (AJEST), 2019)
Virtually, all occupations to some extent have inherent risks. The objective of the study was to assess the role of arsenic (As) in universities’ instructional laboratories indoor settled dust as an occupational carcinogenic risk medium. Dust samples were thus collected from Moi University and University of Eldoret within Uasin Gishu County Kenya, according to standard procedure and As analysis determined using the S1 Titan X-ray fluorescence (XRF) spectrometer. Concentrations ranged from 0.04-349.24 mg/kg while mean As concentrations ranged from 0.424-131.73 mg/kg at ETD and RMD stations, respectively. Mean As concentrations varied significantly and decreased in the order of RMD > EWW > RMR > MC > REW > MSM > EC > ECA> MMW > ETD. Comparison with acceptable ELCR (1 x 10-4 -1 x 10-6) levels indicated that over 50% of the stations were significantly (95 % (CI); p < 0.05) exposed to As CTE and RME carcinogenic risks for both men and women. RMD work-unit posed the highest risk for men and women, respectively. The findings indicate that employees were theoretically exposed to inherent As carcinogenic risks as a result of their work predisposition. The study recommends that appropriate biomarkers such as total urine arsenic be used to ascertain the magnitude of exposure and for occupational exposure monitoring.